[Hindu temple, Port of Spain, Trinidad] - (:unkn) unknown (Pan American, 2010)
Description at back of postcard reads: "Hindu temples are among the interesting attractions of Port of Spain, Trinidad-colorful, polyglot junction of PAA's north, south and west routes."
Colour: White, Red, Yellow, Blue, Rust, Green and Cream Hues; Style: Portrait; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Hindu temples--Trinidad and Tobago; Churches--Trinidad and Tobago; Hinduism--Trinidad and Tobago; East Indians--Trinidad and Tobago; Architecture--Trinidad and Tobago; Ethnic costume--India; Hindu priests--Trinidad and Tobago; Men--Trinidad and Tobago; Tourists--Trinidad and Tobago; Coconut palm--Trinidad and Tobago